The 2′-phenyl cinchonidine thiourea-catalyzed asymmetric addition of alcohols to isatin-derived N-Boc ketimines. Issue 20 (1st November 2015) - Liu, Jing; Zhu, Fang-Meng; Chu, Yun-Bo; Huang, Li-Hong; Zhou, Yi-Feng
Graphical abstract